2022
DOI: 10.1177/21514593221080279
|View full text |Cite
|
Sign up to set email alerts
|

Management of Severe Scoliosis with Pulmonary Arterial Hypertension: A Single-Center Retrospective Case Series Study

Abstract: Aims To determine the impact of anesthesia encountered and to optimize the treatment of perioperative pulmonary arterial hypertension (PAH) in an effort to improve perioperative management and reduce complications. Methods We conducted a retrospective analysis of scoliosis patients with PAH who underwent scoliosis surgery. Results During this period, we identified a total of 22 patients. Their mean age was 22.18 ± 2.11 years. 16 PAH patients (72.72%) received PAH-specific treatment. Only Propofol-based TIVA wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Likewise, direct compression of the myocardium could occur in conjunction with pulmonary involvement. These events can contribute to the development of cardiac consequences in patients with scoliosis 27. It would be beneficial to include cardiac follow-ups in patients with scoliosis to observe any cardiac alterations as scoliosis progresses, ensuring early intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, direct compression of the myocardium could occur in conjunction with pulmonary involvement. These events can contribute to the development of cardiac consequences in patients with scoliosis 27. It would be beneficial to include cardiac follow-ups in patients with scoliosis to observe any cardiac alterations as scoliosis progresses, ensuring early intervention.…”
Section: Discussionmentioning
confidence: 99%
“…15 Previous studies indicated that ~3.04% of the patients undergo spinal osteotomy complicated with PAH. 16 The mechanism of PAH induced by spinal deformity is as follows: in contrast, restrictive ventilation disorder will cause alveolar hypoventilation, which leads to hypoxemia and pulmonary vasoconstriction. In contrast, uneven pulmonary ventilation can lead to regional alveolar hypoxia and induce pulmonary artery contraction to maintain the ventilation/perfusion ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Based on different causes, PAH can be divided into 5 broad categories, and PAH caused by pulmonary disease and/or hypoxia is the important one 15 . Previous studies indicated that ~3.04% of the patients undergo spinal osteotomy complicated with PAH 16 . The mechanism of PAH induced by spinal deformity is as follows: in contrast, restrictive ventilation disorder will cause alveolar hypoventilation, which leads to hypoxemia and pulmonary vasoconstriction.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, direct compression of the myocardium could occur in conjunction to pulmonary involvement. These events can contribute to the development of cardiac consequences in scoliosis patients [27]. It would be beneficial to include cardiac follow-ups in patients with scoliosis to observe any cardiac alterations as scoliosis progresses, ensuring early intervention.…”
Section: Participants With Scoliosis Have Altered Cardiac Diastolic S...mentioning
confidence: 99%